Stepwise activation of SARM1 for cell death and axon degeneration revealed by a biosynthetic NMN mimic - Yinpin Huang; Jun Zhang; Wenbin Zhang; Jie Chen; Sijia Chen; Qincui Wu; Sanduo Zheng; Xiaodong Wang (Proceedings of the National Academy of Sciences, 2025)
Axon degeneration, driven by the NAD + hydrolyzing enzyme SARM1, is an early pathological hallmark of numerous neurodegenerative diseases. SARM1 exists in an inactive form and is activated following nerve injury. However, the precise molecular mechanism underlying SARM1 activation remains to be fully elucidated. In this study, we report the identification of a potent proactivator of SARM1, G10, which is converted into a direct activator (M1) by the enzyme nicotinamide phosphoribosyltransferase. Cryoelectron microscopy structures of SARM1 bound to M1, as well as to M1 and a nonhydrolyzable NAD + analog (1AD), captured two intermediate activation states and the fully active state, revealing a stepwise mechanism of SARM1 activation. Further, introducing a disulfide bond to prevent conformational transitions between the two intermediate states mediated by M1 stabilized SARM1 in its inactive form and blocked M1-induced cell death. Together, these findings propose a sequential, stepwise activation model for SARM1 and offer a framework for developing potential SARM1 inhibitors for the treatment of neurodegenerative diseases.